Static and seismic design of Dry Stone Retaining Walls (DSRWs) following Eurocode standards - Savalle, Nathanaël (2023)
Dry Stone Retaining Walls are structures made of rubble stones assembled without mortar and have been present worldwide for centuries. Today, they still constitute an attractive alternative to building techniques involving higher embodied energy, such as reinforced concrete walls. This study uses a pseudo-static approach to give design recommendations to maintain this built heritage and allow its modern construction. Both non-seismic (Eurocode 7) and seismic (Eurocode 8) cases are addressed. The present work confirms that a seismic design is not critical and is therefore not required for zones with a design acceleration below 0.05g. In addition, this work highlights the significant positive effect of the stone bed inclination and the internal wall face batter. Finally, depending on the wall site conditions and the seismic zone associated with the project, general design recommendations are given to optimise the volume of stones used, which are illustrated in the case of France. These recommendations based on pseudo-static analyses are already usable in practice for low to moderate seismic areas as the required retaining wall dimensions can be easily implemented on-site. In addition, it is also shown that the actual French recommendations for these walls fully comply with Eurocode 7.